COMPREHENSIVE APPROACH TO ASSESSING THE ECONOMIC SECURITY OF ENTERPRISES: ADVANTAGES AND DISADVANTAGES OF NEURAL NETWORK MODELING, CLUSTERING, AND FUZZY LOGIC METHODS - MYROSHNYCHENKO, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article presents a comprehensive analysis of the key determinants of enterprise economic security under the conditions of heightened uncertainty, sectoral turbulence, and the ongoing war in Ukraine. In light of the severe challenges posed by martial law, economic instability, and structural shocks to national industry, the article emphasizes the necessity of a new methodological framework that transcends traditional static models. It argues for the incorporation of intelligent analytical tools-including artificial neural networks (ANNs), Kohonen self-organizing maps (SOMs), and fuzzy logic systems – as part of an integrated, adaptive approach to measuring and enhancing economic security at the enterprise level.Kohonen self-organizing maps (SOMs) are introduced as an additional tool for clustering and segmenting enterprises based on similarity in economic behavior. SOMs are capable of projecting multi-dimensional data into a lower-dimensional space while preserving the topological properties of the original dataset.The article also provides a comparative table of advantages and disadvantages of each method individually and in combination. Neural networks were shown to offer unmatched predictive power but suffer from complexity and opacity. Fuzzy logic offers transparency and flexibility but lacks autonomous learning. Kohonen maps are powerful for visual analysis but require supplementary tools for interpretation.In conclusion, this study makes a significant contribution to the evolving discourse on enterprise security and resilience in crisis conditions. It provides a theoretically grounded, empirically validated, and practically applicable framework for using intelligent technologies in the assessment and enhancement of economic security. The model proposed in the article is positioned not only as a technical tool but also as a strategic asset that supports informed decision-making, fosters adaptive capacity, and promotes sustainable development in the face of adversity. The model’s implementation can significantly improve enterprise strategic foresight.
Keywords: economic security; neural network modeling; clustering; fuzzy logic; enterprise risks; martial law; financial stability; adaptability; intelligent methods